2001
DOI: 10.1103/physreva.64.043801
|View full text |Cite
|
Sign up to set email alerts
|

Recoherence in the entanglement dynamics and classical orbits in theN-atom Jaynes-Cummings model

Abstract: The rise in linear entropy of a subsystem in the N -atom JaynesCummings model is shown to be strongly influenced by the shape of the classical orbits of the underlying classical phase space: we find a one-to-one correspondence between maxima (minima) of the linear entropy and maxima (minima) of the expectation value of atomic excitation J z . Since the expectation value of this operator can be viewed as related to the orbit radius in the classical phase space projection associated to the atomic degree of freed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
10

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 41 publications
2
32
0
10
Order By: Relevance
“…These remarkably different time scales and the extensivity of the entropy have already been mentioned in slightly different contexts in [33] and [37] respectively. Also, other time scales have been established in [35].…”
Section: Coupled Nonlinear Oscillatorsmentioning
confidence: 99%
“…These remarkably different time scales and the extensivity of the entropy have already been mentioned in slightly different contexts in [33] and [37] respectively. Also, other time scales have been established in [35].…”
Section: Coupled Nonlinear Oscillatorsmentioning
confidence: 99%
“…which in contrast to the popular belief [11] is exactly solvable through Bethe ansatz, as we see below. To make the model more physical we should add a field term ω f b † b to the Hamiltonian (19).…”
Section: High Spin Limitmentioning
confidence: 62%
“…Identifying the models in real systems and experimental verification of the related results presented here, especially in many-atom microlasers [25] or in trapped ions away from resonance point [11] would be an important application.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…To date, many aspects of the model have been studied, such as the dynamical properties of quantum entanglement and decoherence [3][4][5][6][7][8], quantum phase transitions (QPT) [2,[9][10][11] and chaotic properties [3,5,9,10,[12][13][14][15]. Furuya et al [3] did the initial work on the entanglement process in a varied version of the model and concluded that for short times, there is a faster increase in decoherence for chaotic initial conditions as compared to regular ones, which have an oscillatory increase.…”
Section: Introductionmentioning
confidence: 99%